Potensi Antibakteri Ekstrak Daging Buah Kelubi (Eleiodoxa conferta) Bangka Belitung Menggunakan Microwave-Assisted Extraction (MAE) - Surtina Surtina (Indonesian Journal of Chemical Research, 2020)
Antibacterial tests were carried out using ethanol extract of kelubi meat (Eleidoxa conferta), extraction using the Microwave-Assisted Extraction method with a ratio of 2: 20 for 30 minutes at 60 °C. Antibacterial tests using diffusion methods with concentrations of 20%, 40%, 60%, 80%, and 100%; positive control of 0.005% amoxillin and DMSO negative control. Antibacterial test results showed that the inhibition zone of ethanol extract in E. coli bacteria with a concentration of 20% was in the moderate category, for a concentration of 40% including the strong category while the concentration of 60%, 80% and 100% was very strong. The inhibition zone of ethanol extract for the S. aureus bacterium with a concentration of 20% is included in the strong category while the concentration of 40%, 60%, 80%, and 100% is categorized as very strong. From these results it can be concluded that the inhibitory zone in Stapylococcus aureus bacteria is greater than that of E. coli bacteria.